Integrating Indonesian Language and Literature in the Merdeka Curriculum to Enhance Literacy and Cultural Appreciation in Secondary Schools - Apriyanto, Sigit; Erlina, Ida Ayu Hani; Herniawati, Ani (CV. Tripe Konsultan, 2025)
The implementation of the Merdeka Curriculum in Indonesia offers opportunities for more contextual, flexible, and student-centred learning. A holistic approach integrating cognitive, affective, and aesthetic aspects enables students not only to master language structures but also to internalise humanistic values and local wisdom embedded in literature. This study examined the integration of Indonesian language and literature learning within the Merdeka Curriculum at the secondary school level as a strategy to strengthen literacy and cultural appreciation. The research draws on 20 scholarly articles published between 2015 and 2025, focusing on educational policy, pedagogical strategies, and empirical studies involving junior and senior high school students from diverse socio-cultural backgrounds. Employing a literature review using the Systematic Literature Review (SLR) method. Data were collected through documentation and analysed thematically to identify patterns, trends, and conceptual contributions. The findings showed that integrating language and literature learning improves literacy skills, deepens cultural understanding, and fosters reflective, meaningful learning experiences. Combining literary texts with language practice enhances critical thinking, empathy, and appreciation of literature in real-life contexts. This integration not only strengthens Merdeka Curriculum implementation but also supports the development of the Pancasila Student Profile. The study suggests further advancement through teacher training, contextual learning media, and supportive educational policies to promote holistic, transformative teaching practices.